Redes ego centradas e os projetos de crowdfunding: uma análise da relação entre as características estruturais da rede social do empreendedor e o sucesso de projetos de financiamento coletivo no Brasil - Zuquetto, Rovian Dill (Universidade do Vale do Rio dos Sinos, 2015)
The crowdfunding is a growing phenomenon that have helped many entrepreneurs to bring their ideas to reality in many areas like arts, cinema, music, technology, web and environment. Understand how the diversity of factors that affect this context and how they affect the crowdfunding project success have been the topic of many researches, but there is a lot of space to map an universe that grows fast around the globe. We look to this phenomenon with a social network lens and how the social network structure of entrepreneurs of crowdfunding affect their projects success. This research is unique in a Brazilian context inside one of the most important platforms in Brasil, the company Catarse. The evidences suggest that the entrepreneurs social network develop an important role to assure the crowdfunding project success, this social network provide the social capital that boost the project in the beginning trough cohesion and the strong ties and the diffusion trough a more polarized network and weak ties available in the entrepreneur social network. The entrepreneurs that can develop their network to have a mix of different connections can provide better changes to the success of their projects. Although there are some limitation in our model, the results shows that the entrepreneurs’ social network in crowdfunding projects can mold the results of it, the importance of social capital is vital to reach success and more studies needs to be developed to understand this phenomenon in different countries and cultures. Crowdfunding have the potential to bring ideas to reality and driven start-ups to big companies, allowing a viable financial source for the entire society.
Keywords: Crowdfunding; Facebook; Catarse; Redes; Empreendedorismo; Networks; Entrepreneurship; ACCNPQ::Ciências Sociais Aplicadas::Administração